Social status and risk-taking in investment decisions - Florian Lindner; Michael Kirchler; Stephanie Rosenkranz; Utz Weitzel (Max Planck Institute for Research on Collective Goods, 2019)
A pervasive feature in the finance industry is relative performance, which can include extrinsic (money), intrinsic (self-image), and reputational (status) motives. In this paper, we model a portfolio decision with two assets and investigate how reputational motives (i.e., the public announcement of the winners or losers) influence risk-taking in investment decisions vis-a-vis intrinsic motives. We test our hypotheses experimentally with 864 students and 330 financial professionals. We find that reputational motives play a minor role among financial professionals, as the risk-taking of underperformers is already increased due to intrinsic motives. Student behavior, however, is mainly driven by reputational motives with risk-taking levels that come close to those of professionals when winners or losers are announced publicly. This indicates that professionals show higher levels of intrinsic (self-image) incentives to outperform others compared to non-professionals (students), but a similar behavior can be sparked among the latter by adding reputational incentives.
Keywords: G02; G11; D03; C93; 330; experimental finance; behavioral economics; investment game; rank incentives; social status; reputational motives